2007
DOI: 10.3133/ofr20071047srp028
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure and evolution of the Mawson Sea, western Wilkes Land margin, East Antarctica

Abstract: This study is based on about 4000 km of MCS, magnetic and gravity data as well as 10 sonobuoys collected by the 2005 Russian Antarctic Expedition in the Mawson Sea and adjacent Australian-Antarctic basin between 102°E and 115°E. Major identified tectonic provinces and features of the study region include: 1) A marginal rift about 300 km wide which developed as a result of extreme crustal extension and unroofing of the upper mantle, and 2) An oceanic basin with the crust of not older than 81 Ma, which is charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Viewed in this framework, some seismic reflection interpretations make more sense than others. The COT interpretations of Leitchenkov et al (2007) and Close et al (2009) provide self-consistent explanations for a range of geophysical observations, including seismic reflection data and stratigraphy as well as gravity and magnetic anomalies. Significantly, in these interpretations COT boundaries do not cross-cut any linear magnetic anomalies, and are also consistent with the interpretation of Blevin and Cathro (2008) for the Australian margin -together yielding a consistent pattern of conjugate magnetic anomalies recorded in the crust of the western Bight Basin and western Wilkes Land margins.…”
Section: Accepted Manuscriptmentioning
confidence: 72%
See 2 more Smart Citations
“…Viewed in this framework, some seismic reflection interpretations make more sense than others. The COT interpretations of Leitchenkov et al (2007) and Close et al (2009) provide self-consistent explanations for a range of geophysical observations, including seismic reflection data and stratigraphy as well as gravity and magnetic anomalies. Significantly, in these interpretations COT boundaries do not cross-cut any linear magnetic anomalies, and are also consistent with the interpretation of Blevin and Cathro (2008) for the Australian margin -together yielding a consistent pattern of conjugate magnetic anomalies recorded in the crust of the western Bight Basin and western Wilkes Land margins.…”
Section: Accepted Manuscriptmentioning
confidence: 72%
“…4). Leitchenkov et al (2007); outermost COT -Colwell et al (2006). However, the most oceanward interpretation of continental crust extent of Colwell et al (2006) should be treated with caution, as the authors themselves noted.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as a consequence of the thermal state and rheology of the lithosphere (Cannat et al, 2019), melt production might vary significantly along strike, with ascending melts either being erupted along volcanic‐rich segments or forming impregnated plagioclase‐peridotites along magma‐poor segments. In both the Bight Basin and conjugate Wilkes Land margin, linear magnetic anomalies (e.g., Golynsky et al, 2012) extending for >1,000 km are observed across regions which have been interpreted as continental crust, exhumed continental mantle, and “proto‐oceanic” crust (e.g., Close et al, 2009; Colwell et al, 2006; Gillard et al, 2015; Leitchenkov et al, 2007). Evidence of magmatism during mantle exhumation along Seamount B thus suggests that many magnetic anomalies, including C34y and C33o, but also extending to C24o and C20y (Tikku & Candes, 1999; Whittaker et al, 2007) might result from sparse volcanic and shallow magmatic additions to the exhumed (subcontinental or oceanic) mantle domain (e.g., Bronner et al, 2014) as a consequence of alternating magmatic and nearly amagmatic segments (e.g., Cannat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, the sparse sampled basement material along the Australian‐Antarctic margins leaves the nature and width of OCTs ambiguous. Interpretations of geophysical data suggest up to 150 km of discrepancy when defining the initiation of unequivocal oceanic crust (e.g., Close et al, 2009; Colwell et al, 2006; Gillard et al, 2015; Leitchenkov et al, 2007). This leads to conflicting interpretations regarding the nature of magnetic anomalies, whether they can be used as isochrons for plate tectonic reconstructions, and the timing of the rift to drift transition (c.f.…”
Section: Introductionmentioning
confidence: 99%